Impact of Janani Suraksha Yojana on institutional delivery in Empowered Action Group States, India - Paul, Lopamudra; Chellan, Ramesh (South East Asia Journal of Public Health, 2014)
The National Population Policy (NPP) in India defined goal to increased institutional delivery and reducing Maternal Mortality Ratio (MMR). Therefore, National Rural Health Mission (NRHM) aimed to increased expenditure to provide primary health care services to poor households in rural India through Janani Surakshya Yojana (JSY), which provide referral transport, escort and improved hospital care for institutional deliveries. The study concludes from District Level Household Surveys (DLHS)-2 and 3 data that Janani Surakshya Yojana undoubtedly contributed to a tremendous improvement in institutional delivery. Accredited Social Health Activist (ASHA), found as an effective link between the Government and the poor pregnant women to provide information on Janani Surakshya Yojana. States like Madhya Pradesh, Odisha and Rajasthan have an impressive rise in institutional delivery and also high percentage of women received financial benefits through the JSY. Planned im-plementation of programme through NRHM may help achieve the goals of NPP 2000 and hence Millennium De-velopment Goal (MDG)-5 to save life of millions mothers and newborn in India. DOI: http://dx.doi.org/10.3329/seajph.v3i2.20033 South East Asian Journal of Public Health Vol.3(2) 2013: 4-18